MATERIAIS VÍTREOS E LUZ: PARTE 2 - Marcelo Nalin; Sidney J. L. Ribeiro; Danilo Manzani; Rogéria Rocha Gonçalves; Gael Poirier; Fabia Castro Cassanges; Christiano J. S. de Matos; Cleber R. Mendonça; Leonardo de Boni; Lino Misoguti; Oscar Malta; Yannick Ledemi; et al. (Química Nova, 2016)
In this second part it will be discussed some photonic applications of glassy and glass ceramic thin films which can be used as planar waveguides. Some photonic applications require certain specifications of glass, which can be quantified by studying the nonlinear optical properties of the materials. Therefore, a brief introduction of these phenomena is discussed, as well as the use of femtosecond lasers to manipulate the composition or for the preparation of waveguides into glasses. Finally, the article will address a brief introduction on microstructured optical fibers and commercial application prospects for these devices.